The Urgency of Classical Learning Motivation in the Millennial Era: Al-Zarnuji's Perspective - Torikhul Wasyik; Abdul Muhid (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
Student learning outcomes in the millennial era have experienced a decline in learning achievement. Among them is a lack of motivation in students, and many Islamic boarding schools in Indonesia use ta'lim muta'allim in their lessons to motivate their students. This article aims to identify and summarize the motivation conveyed by Imam Zarnuji in the Book of ta`lim mutaalim which is suitable for the millennial era. The research method used is a descriptive qualitative method using literature studies. Data techniques by conducting studies of books, notes, article journals, notes that support each other. Data sources are divided into several types, namely: a) Primary data from the Book of ta'lim muta 'allim by Imam Al-Zarnuji b) Secondary data is complementary data that can be used as a reference in journals including relevant literature. This article results indicate that the past (Imam zarnuji) motivation is useful for the millennial era 1) Twenty-eight intrinsic motivations include Intention, patience, sincerity, and high aspirations. 2) seven extrinsic incentives should seek knowledge, find teachers and good friends, and stay away from immorality. Suggesting further research to measure what percentage of intrinsic and extrinsic motivation can increase achievement and enthusiasm for learning.